PENGARUH PROMOSI, KEPERCAYAAN, DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN MELALUI MARKETPLACE SHOPEE PADA MAHASISWA JURUSAN MANAJEMEN BISNIS SYARIAH ANGKATAN 2018 UIN SAYYID ALI RAHMATULLAH TULUNGAGUNG - Windy Widiyawati; Siswahyudianto Siswahyudianto (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This research aims to analyze the effect of promotion, trust, and online customer reviews on purchasing decisions through the Shopee marketplace for students majoring in MBS class 2018 UIN Sayyid Ali Rahmatullah Tulungagung. The research method used in this research is quantitative method with associative research type. The technique used in sampling is non-probability sampling with purposive sampling. The sample studied was 100 respondents from students majoring in MBS class 2018 UIN Sayyid Ali Rahmatullah Tulungagung and had made purchases through Shopee. The analysis used is using the instrument test (validity test, reliability test), classical assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression test, hypothesis test (partial (t) test, simultaneous (f) test), and coefficient of determination test (R2) using the SPSS application. The results of this study are partially (1) promotion has a positive and significant effect on purchasing decisions, (2) trust has a positive and significant effect on purchasing decisions, (3) online customer reviews have a positive and significant effect on purchasing decisions, (4) promotion, trust, and online customer reviews simultaneously have a positive and significant effect on purchasing decisions through the Shopee marketplace for students majoring in MBS class 2018 UIN Sayyid Ali Rahmatullah Tulungagung